The hobbit. The battle of the five armies - Jackson, Peter, 1961-; Walsh, Fran, 1959-; Boyens, Philippa; Toro, Guillermo del, 1964-; McKellen, Ian; Freeman, Martin, 1971-; Armitage, Richard, 1971-; Lilly, Evangeline, 1979-; Evans, Luke, 1979-; Pace, Lee, 1979-; Cumberbatch, Benedict, 1976-; Stott, Ken, 1955-; et al. ([Burbank, CA] : Warner Bros. Entertainment Inc., 2015)
"The epic conclusion to the adventures of Bilbo Baggins. The dragon Smaug rains his fiery wrath down upon the defenseless men, women, and children of Lake-town. Obsessed above all else with his reclaimed treasure, Thorin sacrifices friendship and honor to hoard it as Bilbo attempts to make him see reason."--
Part title from container; languages from language menu.
Based on the novel by J.R.R. Tolkien.
Originally released as a motion picture in 2014.
This disc originally part of a combo pack.
Special features: New Zealand: home of Middle-Earth - Part 3.
Ian McKellen, Martin Freeman, Richard Armitage, Evangeline Lilly, Luke Evans, Lee Pace, Benedict Cumberbatch, Ken Stott.
Keywords: Tolkien, J. R. R. -- 1892-1973 -- Film adaptations; Hobbits (Fictitious characters) -- Drama; Imaginary wars and battles -- Drama; Feature films; Fiction films; Action and adventure films; Film adaptations; Video recordings for the hearing impaired